Conflict, healthcare and professional perseverance: A qualitative study in a remote hospital in an Anglophone Region of Cameroon. - Juste Ongeh Niba; Stewart Ndutard Ngasa; Neh Chang; Eric Sanji; Anne-Marie Awa; Therence Nwana Dingana; Carlson Babila Sama; Leticia Tchouda; Mekolle Enongene Julius (Public Library of Science (PLoS), 2022)
Armed conflicts are a major contributor to global disease burden owing to their deleterious effects on health and healthcare delivery. The Anglophone crisis in Cameroon is one of the ongoing conflicts in Sub-Saharan Africa and has led to massive displacement of healthcare workers (HCWs). However, some HCWs have stayed back and continued working. An understanding of their experiences, perspectives and professional perseverance is lacking. We designed a phenomenological study using Focused Group Discussions (FGDs) and in-depth interviews to: understand the experiences of 12 HCWs in a remote hospital in the North West region of Cameroon with armed groups; evaluate how it affects healthcare delivery from HCWs perspective and examine HCWs coping mechanisms during the conflict with a view of informing HCW protection policies in conflict zones. Results revealed that HCWs go through all forms of violence including threats, assaults and murders. Overall insecurity and shortage of health personnel were major barriers to healthcare delivery which contributed to underutilization of healthcare services. Participants observed an increase in complications due to malaria, malnutrition and a rise in maternal and infant mortality. The hospital management and Non-Governmental Organizations (NGOs) played an essential role in HCWs adaptation to the crisis. Nevertheless they unanimously advocated for a cease fire to end the conflict. In the meantime, passion for their job was the main motivating factor to stay at work.